Effects of tool rake angle and tool nose radius on surface quality of ultraprecision diamond-turned porous silicon. (January 2019) - Heidari, Mehdi; Akbari, Javad; Yan, Jiwang
Highlights: Tool geometry has a profound impact on surface quality of machined porous silicon. A negative rake angle propagate microcracks extensively near the pore walls. Cutting pressure of porous silicon is reduced as rake angle decreased. Using a tool with a bigger nose radius suppressed brittle fractures. Abstract: This paper presents an investigation of the effects of tool rake angle and nose radius on the surface quality of ultraprecision diamond-turned porous silicon. The results showed that as rake angle decreases, the high-stress field induced by the tool edge increases, causing microcracks to propagate extensively near the pore walls. As a result, the ductile-machined areas shrank under a negative tool rake angle. On the other hand, brittle fracture occurred around pores released cutting pressure significantly. These trends of rake angle effects are distinctly different from those in the cutting of non-porous silicon. Finite element simulation of stress in the cutting area agreed with the experimental results. The results also indicated that using a tool with a bigger nose radius suppressed brittle fractures around the pore edge and improved surface quality. Raman spectroscopy of the ductile-machined surfaces revealed that the amorphization of the subsurface layer became more significant when decreasing tool rake angle or increasing tool nose radius. By choosing the optimal tool geometry, a high quality surface can be achieved on porous silicon, which demonstrates the capability of the diamond turning process to fabricate high-precision components.